Ageing causes an aortic contractile dysfunction phenotype by targeting the expression of members of the extracellular signal‐regulated kinase pathway. Issue 5 (18th February 2022) - Nicholson, Christopher J.; Xing, Yi; Lee, Sophie; Liang, Stephanie; Mohan, Shivani; O'Rourke, Caitlin; Kang, Joshua; Morgan, Kathleen G.
Abstract: The extracellular signal‐regulated kinase (ERK) pathway is a well‐known regulator of vascular smooth muscle cell proliferation, but it also serves as a regulator of caldesmon, which negatively regulates vascular contractility. This study examined whether aortic contractile function requires ERK activation and if this activation is regulated by ageing. Biomechanical experiments revealed that contractile responses to the alpha1‐adrenergic agonist phenylephrine are attenuated specifically in aged mice, which is associated with downregulation of ERK phosphorylation. ERK inhibition attenuates phenylephrine‐induced contractility, indicating that the contractile tone is at least partially ERK‐dependent. To explore the mechanisms of this age‐related downregulation of ERK phosphorylation, we transfected microRNAs, miR‐34a and miR‐137 we have previously shown to increase with ageing and demonstrated that in A7r5 cells, both miRs downregulate the expression of Src and paxillin, known regulators of ERK signalling, as well as ERK phosphorylation. Further studies in aortic tissues transfected with miRs show that miR‐34a but not miR‐137 has a negative effect on mRNA levels of Src and paxillin. Furthermore, ERK phosphorylation is decreased in aortic tissue treated with the Src inhibitor PP2. Increases in miR‐34a and miR‐137 with ageing downregulate the expression of Src and paxillin, leading to impaired ERK signalling and aortic contractile dysfunction.